Citizen's income schemes: An amendment, and a pilot project - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2016)
This is an addendum to EUROMOD working paper EM 5/16, revisiting an illustrative Citizen's Income scheme developed in that paper. It makes a necessary adjustment to the scheme, and then develops a method for organising a Citizen's Income pilot project.
Keywords: C80; H53; H55; I38; R20; 330; Citizen's Income; microsimulation model; pilot project